Ultrasonic wave propagation in the corner section of composite laminate structure: Numerical simulations and experiments. (May 2015) - Ito, Junta; Biwa, Shiro; Hayashi, Takahiro; Kuraishi, Akira
Abstract: Two-dimensional finite element simulations and experiments are presented to examine the ultrasonic wave propagation behavior in the corner section of CFRP (carbon fiber reinforced plastics) laminate structures. The numerical model consists of a right-angle corner section of CFRP laminate immersed in water and subjected to the ultrasonic wave incidence from its inner or outer side. The anisotropic stiffness constants of the unidirectional CFRP are identified experimentally and used to model the curved laminate structure. A commercial finite element analysis code is used to compute the reflection waveforms in the pulse-echo mode, and the effect of the laminate stacking sequence and the wave incidence direction is examined. It is shown that the reflection waveforms for the wave incidence from the outer side of the corner qualitatively resemble those for the plane laminate except that the echo signals of the former are substantially weaker. The numerical simulations are shown to well reproduce the qualitative features of experimental reflection measurements performed for the corner sections of 16-ply CFRP laminate. Experimental results indicate that the porosity content of the corner section can be estimated by the amplitude ratio of the surface and the back-wall echoes when a curvature-dependent calibration relation is properly used.